Antimicrobial resistance and stewardship: What do pharmacists know and practice in a major Nigerian tertiary health facility: A cross-sectional study - Alero Ann Roberts; Indu Das; Babatunde A. Akodu; John Olatunde Aderemi; Sharon Chioma Ajudua; Chioma S. Osuagwu; Iretiolu B. Fajolu; Patricia Eyanya Akintan; Temilola Felicia Olufohunsi; Phillip Olayiwola Oshun; Olubusola Olugbake; Rebecca Oritsemaje Soremekun; et al. (Journal of Clinical Sciences, 2024)
Background: Multidrug-resistant bacterial infections are still a global challenge and successful antimicrobial stewardship (AMS) requires multidisciplinary collaborative partnership. Studies have highlighted the knowledge and perceptions of pharmacists, but there is a paucity of data about practices of pharmacists in teaching hospitals in Nigeria. We set out to determine the knowledge and practices of pharmacists in a major tertiary health facility (THF) in Lagos, Nigeria, before starting an AMS intervention program. Methods: This cross-sectional survey used electronic forms to find out the knowledge and practices of pharmacists employed in a large tertiary health facility. Data were collected during a Commonwealth Partnerships for AMS program to support low- and middle-income countries to produce antimicrobial consumption surveillance data, quality improvement initiatives, and infection prevention and control (IPC) processes. Results: Two-thirds of respondents knew that antibiotics were effective against bacteria, and 48.6% knew the causes of antimicrobial resistance. Almost all (97.1%) agreed that AMS must be done, IPC is important, and they were confident to point out inappropriate prescribing. Three-quarters had advised colleagues or been involved in AMS activities; however, 62.9% had fully or mostly changed their practices based on information received, and 26.5% had participated in World Antibiotic Awareness Week. Conclusion: There are still gaps in knowledge and practices, which underscore the need to entrench regular training on the job. However, there is overall awareness of AMS and a desire for it to be carried out at all levels. Pharmacists are useful for choosing appropriate antibiotics and can play a vital role in AMS.